Lipid accumulation of Chlorella pyrenoidosa under mixotrophic cultivation using acetate and ammonium - Liu, L.; Zhao, Y.; Jiang, X.; Wang, X.; Liang, W.
Acetate and ammonium were used as organic carbon and nitrogen sources, respectively, during mixotrophic cultivation of Chlorella pyrenoidosa. Cell growth, content of neutral lipid (NL), productivity of biomass and total lipid, and fatty acid profiles were investigated. Results showed that C. pyrenoidosa could endure high concentrations of NH4+-N (100-200 mg/L)and immediately entered logarithmic growth, when the culture media contained 2.0-10.0 g/L NaAc. The 2.0-10.0 g/L NaAc in the media also resulted in the NL content of 1.87-3.05 mg/109cells, much higher than 0.5 mg/109cells of the controls. The maximum productivities of biomass and total lipid were achieved under 50 and 10 mg/L NH4+-N respectively when the 2.0 g/L NaAc was dosed. The fatty acids were mainly composed of C16:0, C16:1, C18:0, and C18:1 under the mixotrophic cultivation, with the higher saturation compared to the controls.
Keywords: ACETATE; AMMONIUM; BIOFUEL; LIPID ACCUMULATION; MICROALGAE